American beauty - Ball, Alan; Mendes, Sam; Cohen, bruce; Jinks, Dan; Spacey, Kevin; Bening, Annette; Dreamworks Pictures ([Universal City, CA] : Dreamworks Home Entertainment, 2000)
When midlife crisis hits, Lester Burnham's fascination with a young girl spurs him to make some major changes in his life
Winner of 5 Academy Awards (1999): Best Picture, Best Actor (Kevin Spacey), Best Director, Best Original Screenplay, and Best Cinematography
Acquisition for KPI (Kelab pencinta Ilmu)
Title from title screen
Also available in DVD Format
Photography, Conrad L. Hall; editors, Tariq Anwar and Chris Greenbury; music, Thomas Newman
Cast: Annette Bening, Kevin Spacey, Wes Bentley, Thora Birch, Chris Cooper, Peter Gallagher, Allison Janney, Mena Suvari
Keywords: Suburban life -- United States -- Drama; Midlife crisis -- Drama; Feature films